1985
DOI: 10.1159/000115756
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Albumin, Immunoglobulins, and Glucose in Cerebrospinal Fluid and Serum of Patients with Disorders of the Central Nervous System

Abstract: The data of 772 patients were analyzed for albumin, immunoglobulins, glucose, and cell counts in cerebrospinal fluid and serum in healthy controls and in patients with various neurological disorders. Using laser-nephelometric end-point determination the IgG/albumin index was established for controls; a value smaller than 0.85 was considered normal. This index was used to distinguish between impairment of the blood-brain barrier and thecal synthesis of immunoglobulins. No correlation was observed between glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
2
1
0
Order By: Relevance
“…Our IgG levels in CSF from non-MS controls are similar to those found by competitive enzyme immunoassay (8). Although the latter did not quantitate IgG or albumin levels in MS CSF, our values for IgG and albumincorrelate well with those reported by nephlometry (15).…”
Section: Discussionsupporting
confidence: 90%
“…Our IgG levels in CSF from non-MS controls are similar to those found by competitive enzyme immunoassay (8). Although the latter did not quantitate IgG or albumin levels in MS CSF, our values for IgG and albumincorrelate well with those reported by nephlometry (15).…”
Section: Discussionsupporting
confidence: 90%
“…They based this proposal on the results of a small study (34 patients with cerebral infarction, 10 of whom had blood-CSF barrier damage), in which they found a relatively higher increase in CSF/S IgG ratio than in CSF/S albumin ratio with increasing val ues for the CSF/S albumin ratio. Other studies have not found such a relative increase in CSF/S IgG ratio in patients with cerebrovascular disease [14]. In the present study, the relation between the CSF/S albumin ratio and the CSF/S IgG ratio was linear (and almost identical) …”
Section: Resultssupporting
confidence: 72%
“…Regarding the protein electrophoretic patterns of dogs affected by chronic canine distemper, the elevation in gamma-globulin fractions is a consequence of an increased intrathecal synthesis of immunoglobulins, as described in several disorders in human beings such as multiple sclerosis and subacute sclerosing panencephalitis ( OSENBRUCK et al, 1985;SORJONEN, 1987).…”
Section: Discussionmentioning
confidence: 99%